2000
DOI: 10.1046/j.1460-9568.2000.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

The chondroitin sulphate proteoglycan brevican is upregulated by astrocytes after entorhinal cortex lesions in adult rats

Abstract: The chondroitin sulphate proteoglycan brevican is one of the most abundant extracellular matrix molecules in the adult rat brain. It is primarily synthesized by astrocytes and is believed to influence astroglial motility during development and under certain pathological conditions. In order to study a potential role of brevican in the glial reaction after brain injury, its expression was analysed following entorhinal cortex lesion in rats (12 h, 1, 2, 4, 10, 14 and 28 days and 6 months post lesion). In situ hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
2
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 50 publications
4
69
2
3
Order By: Relevance
“…In addition, NG2 immunoreactivity was associated with blood vessels in the lesion core. Other studies have similarly demonstrated the presence of CSPGs at sites of CNS injury, including NG2 (Levine, 1994), neurocan (McKeon and Buck, 1997), phosphacan (Barker et al, 1996), versican McKeon et al, 1999) and brevican (Jaworski et al, 1995;Haas et al, 1999;Thon et al, 2000). In vitro, and at sites of CNS injury, CSPGs are generally produced by reactive glia: astrocytes are thought to make neurocan and phosphacan while oligodendrocyte precursors make NG2, neurocan, and phosphacan (Maurel et al, 1994;Faissner et al, 1994;Engel et al, 1996;Meyer-Pullitz et al, 1996;Nishiyama et al, 1999;Asher et al, 2000a).…”
Section: Chondroitin Sulphate Proteoglycansmentioning
confidence: 86%
“…In addition, NG2 immunoreactivity was associated with blood vessels in the lesion core. Other studies have similarly demonstrated the presence of CSPGs at sites of CNS injury, including NG2 (Levine, 1994), neurocan (McKeon and Buck, 1997), phosphacan (Barker et al, 1996), versican McKeon et al, 1999) and brevican (Jaworski et al, 1995;Haas et al, 1999;Thon et al, 2000). In vitro, and at sites of CNS injury, CSPGs are generally produced by reactive glia: astrocytes are thought to make neurocan and phosphacan while oligodendrocyte precursors make NG2, neurocan, and phosphacan (Maurel et al, 1994;Faissner et al, 1994;Engel et al, 1996;Meyer-Pullitz et al, 1996;Nishiyama et al, 1999;Asher et al, 2000a).…”
Section: Chondroitin Sulphate Proteoglycansmentioning
confidence: 86%
“…Neurons do not attach well to surfaces coated with brevican and do not extend axons toward a surface containing this chondroitin sulfate proteoglycan (53,54). In vivo, brevican is expressed around the boundaries of the rostral migratory stream (55) and is a major up-regulated component of the glial scar after neural injury (56,57), limiting axonal extension and probably limiting neuroblast and astrocyte motility (53,55). Thus, brevican seems to function in the neural matrix predominantly as a stop signal for motile neural cells or extending neurites.…”
Section: Discussionmentioning
confidence: 97%
“…Recombinant portions of aggrecan (mAC-IGD: residues 368 -481 and mAC-GAG: 1678 -1896; Swiss-Prot Q61282) and neurocan (mNC-C: residues 645-944; Swiss-Prot P55066) served as antigens for the immunization of guinea pigs. Rabbit antisera against rat brevican (Thon et al, 2000) and TnR (Day et al, 2004) were kind gifts of Takako Sasaki (University of Erlangen, Erlangen, Germany) and Anders Aspberg (University of Lund, Lund, Sweden), respectively.…”
Section: Methodsmentioning
confidence: 99%